PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP PENGGUNAAN INFORMASI KEUANGAN DAERAH (Studi Pada Kabupaten Keerom) - Sopamena, Gracelia Christi; Kambuaya, Maylen K Petra; Arunglamba, Rama Soyan (Fakultas Ekonomi, Universitas Cenderawasih, 2020)
Research is intended to measure the effect of reporting the financial area and accessibilitiesfinancial report against the user information about the financial area ie Parliament, employees ofthe inspectorate, and society. This analysis uses two variables: the dependent variable or the userof regional and independent financial information or presentation of regional financial statements.The sample of this research is the Keerom Regency DPRD as the main user of financial reports,Keerom Regency Inspectorate employees, Keerom Regency BAPPEDA employees, and theProvincial BPK. Samples were done by using the snowball method. This research is a quantitativestudy with a sample size of 83. Data was obtained through a questionnaire distributed directly tothe DPRD, inspectorate employees, BAPPEDA, and BPK employees. The analytical method used inthis research is the Partial Least Square (PLS) method.The results of this study indicate that: 1. The presentation of regional financial statements has asignificant effect on the use of regional financial information. 2. Regional Financial Accessibilitydoes not have a significant effect on the Use of Regional Financial Information. 3. SimultaneousPresentation of Regional Financial Statements and Regional Financial Accessibility Affect the Useof Regional Financial Information.